2002
DOI: 10.5713/ajas.2002.671
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the Sultanate of Oman of Small Ruminants Given Date Byproducts-Urea Multinutrient Blocks

Abstract: This study investigated the use of multinutrient blocks (MNB) composed of 35% date syrup, 35% date syrup byproducts, 10% date fronds, 7% urea, 7% cement and 6% common salt for growing small ruminants, as partial substitute for the roughage component of the diet (Rhodes grass hay) and its effect on feedlot performance and economics of feeding. Eight growing local Omani goats and 8 sheep (each about one year old) were used in this study. Mean body weights for goats and sheep (kg), respectively were 21.1±4.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The variability in block intakes in sheep and goats may rely on FB formulation and other factors such as animal physiological state or breed (Sansoucy, 1986). Taking into account the amount of cereals included in the concentrate and in FB used in the present work, the average intakes, and the cost of diet ingredients, a reduction of 32% in feeding cost may be achieved with FB containing diets in agreement with others (El Hag et al, 2002;Molina-Alcaide et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…The variability in block intakes in sheep and goats may rely on FB formulation and other factors such as animal physiological state or breed (Sansoucy, 1986). Taking into account the amount of cereals included in the concentrate and in FB used in the present work, the average intakes, and the cost of diet ingredients, a reduction of 32% in feeding cost may be achieved with FB containing diets in agreement with others (El Hag et al, 2002;Molina-Alcaide et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…El Hag et al (2002) found that it was economically viable to use FB-containing by-products and urea for sheep and goats because the cost per kilogram of grain was reduced by 38% as compared with the control diet (grass hay and concentrate).…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure proper hardening of the LB, the BV of the molasses should be at least 85% [39]. Because molasses is expensive, LBs without molasses have been developed in many countries [40,41].…”
Section: Molassesmentioning
confidence: 99%